PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA PT CHIP MOTOR INDONESIA - Mutmainnah, Mutmainnah; Dimyati, Ahmad (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to determine the effect of partially and simultaneously between Price and Promotion of Purchasing decisions on PT CHIP Motor Indonesia. This research method is quantitative descriptive research type and uses data collection methods using a questionnaire instrument. The population in this study amounted to 523 respondents and the sample in this study amounted to 84 respondents and used random sampling techniques. While the data analysis method uses statistical formulas namely by testing the instrument validity test, reliability test, product moment correlation coefficient test, determination coefficient test, autocorrelation test, heterocedasticity test, multiple linear regression test, and hypothesis testing.The results of the study are based on data analysis, there is a significant positive effect between price on the purchase decision of PT CHIP Motor Indonesia with t count> t table (1,848> 1,664) and sig <0.05 (0.68 <0.05) then Ha is rejected Ho be accepted. There is a significant positive influence between promotion of PT CHIP Motor Indonesia purchasing decisions with the t value> t table (8.782> 1.664) and sig <0.05 (0.000 <0.05) then Ha is rejected Ho is accepted. Simultaneous testing shows Price and Promotion jointly influence the Purchase Decision, this is evidenced by the regression equation Y = 5.388 + 0.224 + 0.675X_2 + e with a constant of 5.388 stating that without the Price (X1) and Promotion (X2) variables then the Purchase Decision (Y) remains formed at 5.388 or if the Price (X1) and Promotion (X2) value = 0 then the Purchase Decision still has a value of 5.388. The results of the determination coefficient R2 = 0.655, meaning that the variable Price (X1) Promotion (X2) has a contribution of 65.5% to the Purchasing Decision (Y) and the remaining 34.5% is influenced by other variables. Hypothesis test results simultaneously indicate the value of f arithmetic> f table that is 76.886> 3.11 and sig <0.05 or 0.000 <0.05 Ha rejected Ho is accepted, which means there is a significant positive influence between Price and Promotion of purchasing decisions at PT CHIP Motor Indonesia.